Penguatan Metode Pembelajaran Menggunakan Aplikasi Edmodo di MTs Al-Mubarok Dusun Suling Desa Bagon Kecamatan Puger - Hairul Huda; Bahar Agus Setiawan (Mujtama': Jurnal Pengabdian Masyarakat, 2021)
Strengthening learning methods through Edmodo, in this activity the first thing offered in the PKM (Community Partnership Program) activity is a program of utilizing information and communication technology in online learning. Online learning used in PKM uses the Edmodo application. Learning using Edmodo makes it easier for teachers and students to interact for the purpose of exchanging information and skills that the teacher possesses. Edmodo is a safe learning platform for teachers, students and schools based on social media. Edmodo provides a safe and easy way for the class to connect and collaborate, share content and access work, grades and school notifications. Our goal is to help educators and teachers harness the power of social media to tailor classrooms for each student. The second is to offer a training program and mentoring in email creation and the operationalization of Edmodo applications that are related to knowledge and skills of educators and students in online learning enviroments. The output of this program include (1) the use of appropriate information technology, namely ,by using the edmodo application, (2) skills in online learning, and (3) making online learning fun and engaging.